2012
DOI: 10.1111/j.1399-6576.2012.02665.x
|View full text |Cite
|
Sign up to set email alerts
|

Parecoxib mitigates spatial memory impairment induced by sevoflurane anesthesia in aged rats

Abstract: Parecoxib mitigates spatial memory impairment induced by sevoflurane anesthesia in aged rats. The synaptic morphometry change may be one of the mechanisms involved in learning and memory deficit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
17
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 33 publications
2
17
0
Order By: Relevance
“…Cognitive function is one of the most basic and important high-level neurological functions in the brain, and it is a basic indicator of the development of human intelligence. Supporting our result, many previous studies also reported the effect of sevoflurane, as well as other anesthetics, on cognitive function (Chen et al, 2001;Millar et al, 2006;Peng et al, 2011;Gong et al, 2012). Interestingly, Peng et al (2011) found that exposure to 1.5% sevoflurane, for as long as 3 d (2 h/d), did not cause significantly different cognitive performance, while exposure to 3% sevoflurane for 2 h was enough to induce cognitive impairment.…”
Section: Discussionsupporting
confidence: 89%
“…Cognitive function is one of the most basic and important high-level neurological functions in the brain, and it is a basic indicator of the development of human intelligence. Supporting our result, many previous studies also reported the effect of sevoflurane, as well as other anesthetics, on cognitive function (Chen et al, 2001;Millar et al, 2006;Peng et al, 2011;Gong et al, 2012). Interestingly, Peng et al (2011) found that exposure to 1.5% sevoflurane, for as long as 3 d (2 h/d), did not cause significantly different cognitive performance, while exposure to 3% sevoflurane for 2 h was enough to induce cognitive impairment.…”
Section: Discussionsupporting
confidence: 89%
“…Sevoflurane also increases levels of the pro-inflammatory cytokine interleukin-6 and tumor necrosis factor-α in the developing mouse brain (7). Anti-inflammatory therapy significantly attenuated the cognitive impairments induced by sevoflurane in young and aged rats (7,41). Our previous study demonstrated that isoflurane induces neuroapoptosis by activating the p38-NF-κB signaling pathway in the brain of developing rats (16).…”
Section: Discussionmentioning
confidence: 84%
“…However, the cognitive impairment induced by anaesthetics may depend on different factors, and it was recently shown that sevoflurane leads to increased interleukin-6 (IL-6) levels and induces neuroinflammation and cognitive disorders in young mice (18). In contrast, Gong et al (4) investigated the effects of a nonsteroid anti-inflammatory drug (parecoxib) on cognitive impairments and they concluded that parecoxib attenuated the nugatory effects induced by sevoflurane in rats. Dexamethasone, which is a widely used agent in the perioperative course to prevent postoperative nausea, vomiting, and inflammatory events, can inhibit the production of IL-6 (19).…”
Section: Discussionmentioning
confidence: 99%
“…The main reason for POCD is not clearly understood, but animal studies have shown that anaesthetic agents can play a role in causing neurodegenerative changes in the brain (3). The cognitive impairment effects of sevoflurane on both aged and young rats have been shown by several researchers, but there is a paucity of data on adult rats (4,5).…”
mentioning
confidence: 99%